2017
DOI: 10.1007/s00425-017-2822-5
|View full text |Cite
|
Sign up to set email alerts
|

UGT79B31 is responsible for the final modification step of pollen-specific flavonoid biosynthesis in Petunia hybrida

Abstract: Main conclusion UGT79B31 encodes flavonol 3- O -glycoside: 2″- O -glucosyltransferase, an enzyme responsible for the terminal modification of pollen-specific flavonols in Petunia hybrida.Flavonoids are known to be involved in pollen fertility in petunia (P. hybrida) and maize (Zea mays). As a first step toward elucidating the role of flavonoids in pollen, we have identified a glycosyltransferase that is responsible for the terminal modification of petunia pollen-specific flavonoids. An in silico search of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 41 publications
2
22
0
Order By: Relevance
“…To investigate the subcellular localizations of Ii UGT71B5a and Ii UGT71B5b, their ORFs were fused with YFP at the C -terminus and transiently expressed in N. benthamiana leaves. As shown in Figure 8C , the signals of both fused proteins presented in the cytoplasm, which was consistent with those of previously reported UGTs, such as Mt UGT72L1, Ph UGT79B31, and Pb UGT72AJ2 ( Pang et al, 2013 ; Knoch et al, 2018 ; Cheng et al, 2019 ). This result also indicated that the cytoplasm might be the subcellular site for lignan glycoside biosynthesis.…”
Section: Resultssupporting
confidence: 92%
“…To investigate the subcellular localizations of Ii UGT71B5a and Ii UGT71B5b, their ORFs were fused with YFP at the C -terminus and transiently expressed in N. benthamiana leaves. As shown in Figure 8C , the signals of both fused proteins presented in the cytoplasm, which was consistent with those of previously reported UGTs, such as Mt UGT72L1, Ph UGT79B31, and Pb UGT72AJ2 ( Pang et al, 2013 ; Knoch et al, 2018 ; Cheng et al, 2019 ). This result also indicated that the cytoplasm might be the subcellular site for lignan glycoside biosynthesis.…”
Section: Resultssupporting
confidence: 92%
“…Sme2.5_06210.1_g00004.1 is annotated as anthocyanidin 3-O-glucosyltransferase. Studies have confirmed that this gene is a terminal modification enzyme of pollen-specific flavonol in Petunia hybrida [55]. The gene was down-regulated when eggplant fruits were exposed to high-temperature stress; then, anthocyanin synthesis decreased, and the expression of 3GT decreased, which is consistent with the findings of previous studies.…”
Section: Discussionsupporting
confidence: 89%
“…Moreover, there is another class of avonoid glycosyltransferases, i.e. avonol 3-O-glycoside: 2''-O glucosyltransferase (3GGT/UGT79), an enzyme responsible for the terminal modi cation of pollen-speci c avonols (Knoch et al 2018). In blueberry, two 3-O glycosyltransferase genes are both up-regulated as fruit matured, while another 5-O glycosyltransferase is down-regulated (Li et al 2019).…”
Section: Discussionmentioning
confidence: 99%